2019
DOI: 10.1007/s00247-019-04549-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered regional myocardial velocities by tissue phase mapping and feature tracking in pediatric patients with hypertrophic cardiomyopathy

Abstract: Background-Hypertrophic cardiomyopathy (HCM) is associated with heart failure, atrial fibrillation and sudden death. Reduced myocardial function has been reported in HCM despite normal left ventricular (LV) ejection fraction. Additionally, LV fibrosis is associated with elevated T1 and might be an outcome predictor.Objective-To systematically compare tissue phase mapping and feature tracking for assessing regional LV function in children and young adults with HCM and pediatric controls, and to evaluate structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Therefore, we showed that the effect of these two pathologies cancel out in our virtual HCM heart to obtain the same peak diastolic velocity as in the control case (Figure 10, right). If we would either further reduce the active force in the LV or less deviate from the control stiffness (or both), we would obtain reduced diastolic velocities in line with [10].…”
Section: Comparison Between Simulated and Clinically Measured Deformamentioning
confidence: 73%
See 4 more Smart Citations
“…Therefore, we showed that the effect of these two pathologies cancel out in our virtual HCM heart to obtain the same peak diastolic velocity as in the control case (Figure 10, right). If we would either further reduce the active force in the LV or less deviate from the control stiffness (or both), we would obtain reduced diastolic velocities in line with [10].…”
Section: Comparison Between Simulated and Clinically Measured Deformamentioning
confidence: 73%
“…Altered Mechanics in HCM Patients Reported in the Literature In HCM patients, global strains and strain rates are reported to be significantly lower [1,11,12], while Ito et al [9] measured preserved (or even increased) circumferential shortening. Furthermore, altered myocardial velocities are detected in HCM patients compared to controls-global and segmental diastolic velocities are decreased and systolic longitudinal velocities were reduced in HCM [10]. In the left atria, a higher minimum volume and a lower peak atrial longitudinal strain was measured in HCM compared to controls [11].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations